Pengaruh Motivasi Berwirausaha dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Siswa SMK Negeri 1 Kepenuhan - Siti Hennida Sari; Sumarno Sumarno; Suarman Suarman (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
This study aims to determine whether there is an influence of entrepreneurial motivation and entrepreneurial knowledge on interest in entrepreneurship. The population is all students who have taken the subjects of Creative Products and entrepreneurship, class XI and XII as many as 170 students. Samples were taken by proportional stratified random sampling as many as 63 students. Data collection techniques using documentation and questionnaires. Data analysis used multiple linear regression analysis. The results showed that the entrepreneurial motivation of students was in the moderate category of 71,4%, entrepreneurial knowledge was in the sufficient category of 73,0%, and interest in entrepreneurship was in the moderate category of 69,8%. Partially, entrepreneurial motivation has a positive and significant effect on interest in entrepreneurship. Entrepreneurial knowledge partially also has a positive and significant effect on interest in entrepreneurship. Entrepreneurial motivation and entrepreneurial knowledge together have a positive and significant effect on interest in entrepreneurship.